Typical esthetic outcomes using 5 different modalities to treat MIH affected teeth: a case series - Natera-Guarapo, Alfredo; Rodríguez-Rodríguez, Mónica; Acosta-de Camargo, Maria Gabriela; Pimentel, Eva; Begoña-Tortolero, María (Revista Facultad de Odontología Universidad de Antioquia, 2023)
Introduction: therapeutic options for incisors affected by Molar Incisor Hypomineralization range from very conservative procedures to those considered to be more invasive. Clinicians must select the appropriate approach, considering the outcomes of the procedures. Methods: this case series presents clinical outcomes of five female patients with aesthetic complaints associated with the Molar Incisor Hipomineralization. Results: macroabrasion, microabrasion and dental vital bleaching were used as combination techniques in three cases. Resin infiltration was indicated for a specific case, considering the oncoming orthodontic treatment. Composite restoration was performed in one patient with posteruptive enamel breakdown. Conclusions: clinicians must select the appropriate approach according to an individualized evaluation of each case, considering factors such as the patient’s expectations, dental age, psychosocial period, the severity of the condition, presence of sensitivity and the presumed aesthetic result of the selected treatment. The advantages and disadvantages of the techniques are presented.